2014
DOI: 10.1037/a0037118
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of college students’ help-seeking intention: A meta-analysis.

Abstract: Associations hetween psychosocial variables and help-seeking intention among college students have often been examined, with inconclusive and sometimes conflicting findings. To consolidate the available research, data from 18 eligible studies comprising a total of 6,839 participants were pooled and meta-analyzed. Attitudes toward seeking professional psychological help and anticipated utility demonstrated the strongest correlations with help-seeking intention. Practice implications are discussed, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 61 publications
4
55
0
Order By: Relevance
“…In keeping with findings of previous researchers (Eisenberg, Gollust, Golberstein, & Hefner, 2007; Li et al, 2014), students with greater mental health literacy and with more positive attitudes toward help‐seeking reported higher help‐seeking intention. Stigma, however, was not associated with students’ help‐seeking intention, contrary to previous findings (Eisenberg et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In keeping with findings of previous researchers (Eisenberg, Gollust, Golberstein, & Hefner, 2007; Li et al, 2014), students with greater mental health literacy and with more positive attitudes toward help‐seeking reported higher help‐seeking intention. Stigma, however, was not associated with students’ help‐seeking intention, contrary to previous findings (Eisenberg et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…This stigma is internalized, which can negatively affect students’ sense of self‐worth (Vogel, Wade, & Haake, 2006) and lead to decreased help‐seeking intention (Hackler et al, 2010) and avoidance of counseling (Vogel, Wester, & Larson, 2007). Similarly, attitudes toward seeking professional counseling are highly correlated with help‐seeking intention among university students (Li, Dorstyn, & Denson, 2014).…”
Section: Student and Parent Influences On Help‐seekingmentioning
confidence: 99%
“…Although the studies evaluated the quality of available social support-a variable that has been linked to service utilization (13,22)-significant associations were found for two measurements only. Similarly, a recent meta-analytic review of college students' intentions to use services reported a nonsignificant correlation between intention and various social support measures (70). It would be valuable to further evaluate predictive effects of individual measurements of social support on young adults' help-seeking patterns, with careful attention to measurement issues.…”
Section: Discussionmentioning
confidence: 99%
“…Counselors can begin to reach out to these students through information sessions on how to receive professional support, where to seek treatment, and the benefits of such treatment. This information can be provided during academic courses, through social media, or electronically through email or school websites (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Counselors can begin to reach out to these students through information sessions on how to receive professional support, where to seek treatment, and the benefits of such treatment. This information can be provided during academic courses, through social media, or electronically through email or school websites (Li et al, 2014). The proportion of students not seeking help is troubling, given that previous studies have found that more than half of the students entering college have experienced a traumatic event (e.g., Frazier et al, 2009;Read, Ouimette, White, Colder, & Farrow, 2011).…”
Section: Implications For College Counselorsmentioning
confidence: 99%